The role of financial factors for European corporate investment. (September 2019) - Mercatanti, Andrea; Mäkinen, Taneli; Silvestrini, Andrea
Highlights: In 2006–2012, European firms' investment did not vary with cash or short-term debt. Yet, during the financial crisis, investment was sensitive to net short-term debt. The findings suggest that firms sought to preserve debt capacity during the crisis. Abstract: Motivated by the debate about the reasons behind the weak investment dynamics in Europe, we provide new evidence on the sensitivity of investment to financial factors and fundamentals before and during the financial and sovereign debt crises. Specifically, controlling for firm-level fundamentals, we evaluate whether European firms' cash holdings and indebtedness affected their investment decisions over the 2006:Q3–2012:Q2 period, and whether their influence changed with the onset of the two crises. Our findings, obtained using a correlated random coefficient panel data model, suggest that investment was primarily determined by firm-level fundamentals over this period. Contrary to earlier studies, we also find that neither cash reserves nor short-term debt, considered separately, were significant determinants of investment, prior and during the two crises. However, there is some evidence of a negative conditional dependence between corporate investment and short-term debt net of cash reserves during the financial crisis, suggesting that firms simultaneously sought to avoid liquidity problems and preserve debt capacity.